TAN MALAKA: COMMUNIST PIONEER OF THE REPUBLIC - Sofyka Putriani; M. Faiz Muzakki; Zainuddin Lubis; M. Raffi Batubara; Rayvand Egintha Sembiring (Journal of International Islamic Law, Human Right and Public Policy, 2025)
Tan Malaka, a revolutionary figure in Indonesian history, is celebrated for his ability to integrate communism, nationalism, and Islamic values. Through his works, Naar de Republiek and Madilog, he laid the foundation for a just and democratic society that emphasizes social welfare and education. This article revisits his contributions to Indonesia's independence movement and explores the contemporary relevance of his ideas in addressing socio-economic disparities. By analyzing his engagement with Islamic movements and critiques of colonial capitalism, this study positions Tan Malaka as not only a communist but also a unifying figure for Indonesia's ideological diversity.